Physical and Electrochemical Investigations into Blended Electrolytes Containing a Glyme Solvent and Two Bis{(trifluoromethyl)sulfonyl}imide-Based Ionic Liquids. Issue 8 (1st January 2017) - Neale, Alex R.; Goodrich, Peter; Hughes, Terri-Louise; Hardacre, Christopher; Ball, Sarah C.; Jacquemin, Johan
Abstract : In this paper, we report on thermophysical and electrochemical investigations of a series of molecular solvent/ionic liquid (IL) binary mixture electrolytes. Tetraethylene glycol dimethyl ether (TEGDME) is utilized as the molecular solvent component in separate mixtures with two bis{(trifluoromethyl)sulfonyl}imide anion based ILs paired with similarly sized cyclic and acyclic alkylammonium cations; 1-butyl-1-methylpyrrolidinium bis{(trifluoromethyl)sulfonyl}imide, [Pyrr14 ][TFSI], or N- butyl- N, N -dimethyl- N -ethylammonium bis{(trifluoromethyl)sulfonyl}imide, [N1124 ][TFSI]. The blending of ILs with select molecular solvents is an important strategy for the improvement of the typically sluggish transport capabilities of these interesting electrolytic solvents. Bulk volumetric and transport properties are reported as a function of temperature and binary mixture formulation; demonstrating the capacity for enhancing desired properties of the IL. Micro-disk electrode voltammetry and chronoamperometry in O2 -saturated binary mixture electrolytes was used to assess the effect of formulation on the solubility and diffusivity of the dissolved gas. In addition, further investigations of the behavior of the O2 redox couple at a GC macro-disk electrode are discussed.